Perbandingan Praktikum Langsung dengan Penggunaan Media Video Pembelajaran Terhadap Kemampuan Analisis Mahasiswa Prodi D3 Analis Kesehatan STIKes Karsa Husada Garut - Gina nafsa mutmaina (STIKes Karsa Husada Garut, 2020)
There are some weekness we found of direct practice learning on D3 Medical Laboratory Technology Program that affect student analytical skill on hematology and blood transfution lesson, that shown half of the participant had low score. This study focuses on the use of learning video media in improving student analytical skill. The purpose of this study is to determine the differences of the students anaytical skill of the direct practice with the learning video media using. This study use quasy eksperimen design, participants included 60 second grade student of D3 Medical Laboratory Technology Program, they are divided in two classes. The first class use direct practice and the second class use learning video media. Data were analyzed using Paired T-test, the result showed Asymp. Sig equal to 0,256> α 0,05 so that there is no differences of the students anaytical skill of the direct practice with the learning video media using. This study suggest that the use of learning video media coexist with the direct practice in the laboratory